1992
DOI: 10.1136/hrt.68.8.192
|View full text |Cite
|
Sign up to set email alerts
|

Continuous wave Doppler echocardiography after surgical repair of coarctation of the aorta

Abstract: Objective-To find how closely pressure gradients across the aortic arch derived from Doppler echocardiography reflect gradients measured by catheter after surgical repair of coarctation of the aorta.Design-Pressure drop across the aortic arch was measured simultaneously by continuous wave Doppler and double lumen catheter in 20 patients with repaired coarctation of the aorta.Results-The peak pressure drop estimated by Doppler was almost invariably higher than the peak to peak gradient measured by catheter, as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Echocardiography undoubtedly improves sensitivity in the diagnosis of residual or recurrent arch obstruction but for an accurate estimation of the degree of obstruction across the repair site an assessment of flow velocities just proximal to the stenosis is essential. 22 In practice, given the geometry of the transverse arch, this measurement is usually very difficult to obtain. 22 Nearly all reported series rely on gradients derived from Doppler interrogation across the site of repair alone, which inevitably leads to an overestimation of the true gradient.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Echocardiography undoubtedly improves sensitivity in the diagnosis of residual or recurrent arch obstruction but for an accurate estimation of the degree of obstruction across the repair site an assessment of flow velocities just proximal to the stenosis is essential. 22 In practice, given the geometry of the transverse arch, this measurement is usually very difficult to obtain. 22 Nearly all reported series rely on gradients derived from Doppler interrogation across the site of repair alone, which inevitably leads to an overestimation of the true gradient.…”
Section: Discussionmentioning
confidence: 99%
“…22 In practice, given the geometry of the transverse arch, this measurement is usually very difficult to obtain. 22 Nearly all reported series rely on gradients derived from Doppler interrogation across the site of repair alone, which inevitably leads to an overestimation of the true gradient. 22 In addition work by De Mey et al, 21 who used simulated models of the aortic arch after coarctation repair, showed that Doppler velocities increased as a manifestation of the change in compliance of the repaired vessel wall in the absence of stenosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aortic arch geometry (i.e. hypoplastic arch), complex flow dynamics in the aortic arch, difficulty in closely aligning the Doppler beam with flow, and inability to measure flow velocity immediately proximal to the site of the surgical repair with continuous wave Doppler probably relate to this finding [28][29][30]. At echocardiography, the presence and the degree of antegrade diastolic flow (diastolic runoff, i.e.…”
Section: Recoarctationmentioning
confidence: 96%
“…With less severe obstruction the signal may be of relatively high velocity but be entirely systolic (fig24). The maximum Doppler and measured catheter gradients correlate poorly with both instantaneous and peak to peak values, whether performed in a primary coarctation51 52 or after surgery 53…”
Section: Coarctation Of the Aortamentioning
confidence: 94%